The Formulation Policy on Corporate Criminal Liability for Criminal Violations of Crimes against Biological Natural Resources and Ecosystems - Jazau Elvi Hasani (Himmah: Jurnal Kajian Islam Kontemporer, 2019)
Indonesia is blessed with extraordinary natural wealth. Article 33 paragraph (3) of the 1945 Constitution stipulates that "Earth, water, and natural resources contained there are controlled by the state and used as much as possible for the prosperity of the people." biological natural resources development can take place in the best possible way with conservation effort. So that the biological natural resources and its ecosystem are always maintained. Development of biological natural resources and their ecosystems is essentially an integral part of sustainable national development. Efforts to conserve biological natural resources and their ecosystems are realized through efforts to analyze and evaluate legislation in the field of support in order to provide future improvements. This paper aims to discuss the corporate criminal liability in Indonesia of conservation of biological natural resources and its ecosystem and suggested revision for this law. Revision of the draft Law About conservation of biological natural resources and its ecosystem has been doing by legislators since 2018. So, the Draft Law is still on processing of revision in the national legislation program (prolegnas). The protection of biological natural resources and its ecosystem becomes the government's main concern because it's regulation still has no deterrent effect for violators. This was proven by many cases about animal trafficking after the rampant raids or raids of protected wildlife traders. The Law No. 5 of 1990 About: Conservation of Biological Natural Resources And the Ecosystem has weakness of violation animal and plants trafficking, the imposition of low fine and low penalty to corporations for criminal violations of crimes against biological natural resources and ecosystems. This law needs substantial revision in the corporate criminal liability of violation poaching of wild animals in order to make the implementation effective.